Calcification Propensity of Serum is Independent of Excretory Renal Function. Issue 1 (December 2017) - Bielesz, Bernhard; Reiter, Thomas; Marculescu, Rodrig; Gleiss, Andreas; Bojic, Marija; Kieweg, Heidi; Cejka, Daniel
Abstract Vascular calcification is a component of cardiovascular disease, which is leading cause of death in patients with chronic kidney disease (CKD). A functional assay (T50-test) measuring the propensity of human serum to calcify associates with mortality and cardiovascular events in CKD patients. Calcification propensity is known to increase with CKD stage. We investigated whether the T50 readout is directly dependent on excretory kidney function (eGFR) or rather explained by deranged parameters of bone and mineral metabolism in the course of CKD. T50, along with markers implicated in calcification and mineral metabolism, were measured in a cross-sectional cohort of 118 patients with CKD stage 1–5. Associations of T50 with measured parameters were analysed and partial correlations performed to test to which extent the association of T50 with eGFR can be attributed to variation of these parameters. T50 correlates with eGFR, but serum levels of phosphate and calcium largely explain this association. Phosphate, magnesium, fetuin A, albumin, bicarbonate, and serum cross-laps but not Parathyroid Hormone or Fibroblast Growth Factor 23 are associated with T50 in multivariate adjusted models. These findings indicate that T50 values depend mainly on the concentration of promoters and inhibitors of calcification in serum, but not excretory kidney function.